Feasibility study towards mobile learning readiness in Management and Science University / Mohd Amlie Sardi Mohd Khomsa - Mohd Khomsa, Mohd Amlie Sardi (2015)
In today's world, learning have changed compare to the conventional way. Mobile technologies have open a wide learning opportunities for the student in higher learning institution who need to keep up with a challenging and complex learning environment. With the fast and vast development of mobile devices especially among the student in Malaysia, institution should look into the possibility of integrating mobile learning in their institution. This thesis discusses about the mobile learning readiness and perception among Management and Science University students which is a private higher learning institution located at Shah Alam. The purpose of this study is to determine and to identify the readiness of the students towards mobile learning implementation at the institution in term of the basic, skill and psychological readiness. The study also will identify the perception of the students on mobile learning from the perspective of differences perception of mobile learning among genders of the students and also to determine the reason that affecting the mobile learning perception. The study will use quantitative analysis approach where the data will be collected using questionnaires. Through this study, most of the students are ready in term of readiness in engaging mobile learning and have the necessary devices and skill required.